L’utile “fine del monopolio delle scienze ecclesiasticistiche”. Prime riflessioni su diritto ecclesiastico e autonomia differenziata delle Regioni ordinarie (Stato, Chiese e pluralismo confessionale, 2019)
SOMMARIO: 1. Premessa - 2. Autonomia differenziata delle Regioni ordinarie e disciplina pattizia dei rapporti tra lo Stato e le confessioni religiose diverse dalla cattolica: così diversi, così uguali - 3. L’utilità del raffronto. Risvolti procedurali e sul piano delle relazioni tra poteri dello Stato - 4. Questioni sostanziali. Unità vs. differenziazione ovvero autonomia vs. eguaglianza - 5. Il diritto ecclesiastico oltre il diritto ecclesiastico (per modo di dire).About the useful “end of the monopoly of the ecclesiasticistic law sciences”. Focusing on the relationships between the ecclesiastical law (of the State) and the differentiation in the autonomy of the ordinary RegionsABSTRACT: Many scholars identify a strong analogy between art. 116, c. 3 (dedicated to the differentiation in the autonomy of the ordinary statute Regions), and art. 8, c. 3 (dedicated to the relationships between the State and the religious denominations different from the Catholic one) of the Italian Constitution. The paper deals with this opinion to underline the importance of the ecclesiastical law (of the State) in order to analyze the doubtful impact of regional autonomy on the equal safeguard of constitutional rights and liberties (first of all, the religious freedom).